Aplikasi Sensor Fusion untuk Mendeteksi Posisi dan Arah Pergerakan Ponsel Pintar di Dalam Ruangan - Gaghana, Rosa Eunike Ruth; Hutagalung, Maclaurin; Sitepu, Herry Imanta (Jurnal Telematika, 2019)
The development of cellular technology and telecommunications is currently giving birth to more specific services, such as location-based smart phone services in the room. Indoor location-based services on mobile require an accurate and real-time position and orientation detection system. One technology that is often used to detect position is the Global Positioning System (GPS), but it is difficult to use to detect indoor positions. The use of accelerometer, gyroscope, magnetometer and GPS on smartphone is one method that can facilitate the system without the need of additional devices. This research combines accelerometer, gyroscope and magnetometer (sensor fusion) to get the latest position and orientation from the smartphone. Data from each sensor has a varied amount of noise and is relatively large so that to get the position and orientation of a smartphone that is minimal noise can use the Kalman filter algorithm on the detection algorithm that will be built in computing software. Transferring sensor data from a smartphone to a computing device can be bridged by a data recorder application that runs on a smartphone. The results of this study are expected to be the basis or new input for indoor location-based services.Perkembangan teknologi dan telekomunikasi seluler saat ini begitu cepat melahirkan layanan yang lebih spesifik, seperti layanan berbasis lokasi ponsel pintar dalam suatu ruangan (indoor positioning system). Layanan berbasis lokasi dalam ruangan pada ponsel membutuhkan sistem deteksi posisi dan orientasi yang akurat dan real-time. Salah satu teknologi yang sering digunakan untuk mendeteksi posisi adalah Global Positioning System (GPS), namun GPS sulit digunakan untuk mendeteksi posisi di dalam ruangan. Penggunaan sensor akselerometer, giroskop, magnetometer dan GPS pada ponsel merupakan salah satu metode yang dapat memudahkan sistem untuk mendapatkan posisi dan orientasi ponsel di dalam ruangan. Sensor-sensor tersebut lebih mudah diakses dan tidak memerlukan perangkat tambahan. Untuk itu, penelitian ini akan melakukan penggabungan sensor akselerometer, giroskop dan magnetometer (sensor fusion) untuk mendapatkan posisi dan orientasi dari ponsel. Data dari setiap sensor memiliki jumlah noise yang bervariatif dan tergolong besar sehingga untuk mendapatkan posisi dan orientasi ponsel yang minim noise dapat menggunakan algoritme filter Kalman pada algoritme deteksi yang akan dibangun. Perpindahan data sensor dari ponsel ke